Pengaruh media sosial dan e-commerce terhadap dunia enterpreneurship - Husna, Faiza Arifatul (Maliki Interdisciplinary Journal, 2023)
The world of entrepreneurship has undergone a significant transformation due to the advancements in social media and e-commerce. Social media facilitates broader market access, while e-commerce presents opportunities for rapid growth with low operational costs. However, these positive impacts are also balanced by negative implications. Intense competition in e-commerce and the risks of privacy infringement and customer fraud pose challenges that need to be addressed. Therefore, entrepreneurs need to fully understand the positive and negative impacts of social media and e-commerce, and take strategic steps to leverage the positives while safeguarding their businesses from negative risks.